Geoelectrical Tomography of Cangar Hot Springs Area, Arjuno-Welirang Complex Stone - Fajar Rakhmanto; Sukir Maryanto; Adi Susilo (Natural B, Journal of Health and Environmental Sciences, 2011)
Have been research geothermal of Arjuno Welirang area of East Java with geoelectric resitivity tomography. Geoelectric tomography was performed by VES (Vertical Electrical Sonding) and Mapping. Acquisition of data totaled 7 points of VES and 4 tracks Mapping was located surrounding the hot springs.Results of geoelectric resistivity modeling showed the resistivity of rock layers the carrier fluid (water) heat <10 Ohm.meter, while a layer of carrier fluid (water) was worth 10-100 Ohm.meter. The hot fluid coming from the direction of CR4 and CR3 are located in the south from the hot springs with a depth of 24.7 meters from the ground CR 3 (see Figure 5) which alleged a layer of sand, with layers of lava rock in the form of heat source at depth 34 meters. Mapping the results of modeling that consists of 4 tracks show around hot springs artifacts crack / crack is suspected as a medium to hot water flow out of the ground surface, precisely located at CANGAR_LINE1.